Public Health Perspectives of Preeclampsia in Developing Countries: Implication for Health System Strengthening - Kayode O. Osungbade; Olusimbo K. Ige (Journal of Pregnancy)
Objectives. Review of public health perspectives of preeclampsia in developing countries and implications for health system strengthening. Methods. Literature from Pubmed (MEDLINE), AJOL, Google Scholar, and Cochrane database were reviewed. Results. The prevalence of preeclampsia in developing countries ranges from 1.8% to 16.7%. Many challenges exist in the prediction, prevention, and management of preeclampsia. Promising prophylactic measures like low-dose aspirin and calcium supplementation need further evidence before recommendation for use in developing countries. Treatment remains prenatal care, timely diagnosis, proper management, and timely delivery. Prevailing household, community, and health system factors limiting effective control of preeclampsia in these countries were identified, and strategies to strengthen health systems were highlighted. Conclusion. Overcoming the prevailing challenges in the control of preeclampsia in developing countries hinges on the ability of health care systems to identify and manage women at high risk.